2001
DOI: 10.2460/ajvr.2001.62.286
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effects of peroxynitrite, polymorphonuclear neutrophils, free-radical scavengers, inhibitors of myeloperoxidase, and inhibitors of nitric oxide synthase on bovine mammary secretory epithelial cells

Abstract: Peroxynitrite, MPO, and histidine are toxic to mammary secretory epithelial cells. Superoxide dismutase and inhibition of MPO activity mitigate these effects. Nitration of MAC-T cell tyrosine residues may be positively associated with viability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…PMA-activated neutrophils in combination with E. coli endotoxins caused release of superoxide. Epithelial damage was also observed [22,135]. Melatonin that scavenges hydroxyl radicals and peroxynitrite reduced neutrophil-induced cytotoxicity dose-dependently [22].…”
Section: Cytotoxic Mediatorsmentioning
confidence: 95%
See 2 more Smart Citations
“…PMA-activated neutrophils in combination with E. coli endotoxins caused release of superoxide. Epithelial damage was also observed [22,135]. Melatonin that scavenges hydroxyl radicals and peroxynitrite reduced neutrophil-induced cytotoxicity dose-dependently [22].…”
Section: Cytotoxic Mediatorsmentioning
confidence: 95%
“…Host lipid peroxidation, initiated by enzymes such as NADPH oxidase and myeloperoxidase, occurs [260]. (2) Neutrophilic degranulation, during which release of proteases occurs as a result of neutrophil trafficking or as a consequence of their phagocytic activity, was also shown to be cytotoxic [2,22,38,135,165,172]. During phagocytosis lysosomes migrate toward the particle being internalised and lysosomal enzymes are released before fusion of the pseudopodia is completed, resulting in the release of lysosomal contents to the outside of the PMN [81].…”
Section: Cytotoxic Mediatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although PMN provide a beneficial effect by eliminating the infectious agent, prolonged exposure of mammary tissue to PMN results in injury to secretory epithelium [29]. One mechanism by which this may occur is through release of toxic oxygen radicals and proteases, agents which are both bactericidal and cytotoxic to host tissue [96,181]. Prolonged inflammation resulting in injury to the mammary secretory epithelium results in scarring and leads to a permanent decrease in milk production [165].…”
Section: Regulation Of Pmn Life Spanmentioning
confidence: 99%
“…Because onset of apoptosis leads to functional impairment of bovine PMN [176], in vivo administration of caspase inhibitors may play an effective role in enhancing the ability of PMN to respond to intramammary infection. Further, caspase inhibitors may have the additional benefit of protecting secretory epithelium from deleterious effects of PMN-derived cytotoxic mediators produced in response to infection [29,96]. In support of a potential therapeutic benefit for caspase inhibitors in mastitis, two studies have shown that prevention of lymphocyte-induced apoptosis with the caspase inhibitor z-VAD enhances survival in a murine model of sepsis [76,77].…”
Section: Cellular Regulation Of Apoptosismentioning
confidence: 99%